The Impact of COVID-19 on Male Semiprofessional Cricket Player’s Mental Health and Performance Following the Resumption of Sporting Events - Lesego S. Malele; Habib Noorbhai (American Journal of Men's Health, 2023)
The ability of a cricket player to manage their mental health helps them to perform optimally. This study investigated how mental health is related to performance of male cricket players during the resumption of sporting events after coronavirus disease 2019 (COVID-19) restrictions. Mental health profiles were established using the Depression, Anxiety, Stress Scale-21 (DASS-21), Athlete Burnout Questionnaire (ABQ), and Satisfaction with Life Scale (SWLS) instruments among male semiprofessional cricket players ( n = 63). Performance metrics included: body fat percentage (BF%), range of motion (ROM), push-abdominal test, crazy catch test, t -test, 40-m sprint, and Cooper’s test. Inferential statistics included Spearman’s correlations with a significance level set at α < .05. Spearman’s correlation reported a statistically significant relationship for SWLS and body mass index (BMI) ( r = −0.263; p = .037) as well as between stress and abdominal test ( r = 0.355; p = .004); crazy catch test ( r = 0.249; p = .049); Cooper’s test ( r = 0.335; p = .009), VO 2 max ( r = 0.308; p = .014), stress and abdominal test ( r = −0.313; p = .012); as well as anxiety and 40-m sprint ( r = 0.488; p = .027). This study provides an important snapshot of how symptoms of mental health are associated with performance. Further research should investigate the relationship between mental health and performance parameters among male players at varied skill levels.